DAMPAK KENAIKAN HARGA BBM TERHADAP PENDAPATAN USAHATANI PADI SAWAH DI DESA BUGEMAN KEC. KENDIT (Studi Kasus Di Desa Bugeman Kecamatan Kendit Kabupaten Situbondo) - Suyono Suyono; Martono Achmar (AGRIBIOS, 2015)
The research objective was to determine whether there are differences in the price of production, rice farming costs, and income before and after the rising fuel on paddy rice farming in the Village District of Kendit Bugeman. The method of determining the area of research is purposive method because bugeman village there are many rice farmers, and the area planted with paddy rice field wide enough between villages in the subdistrict. gird, so enough to be used as a sampling study. Cropping patterns in the village bugeman namely rice throughout the year, due to the availability of adequate water in the dry season. The results showed that the effect of rising fuel prices affect the price of production, total expenses, and revenue Bugeman rice farming in the Village District of Kendit with an average acquisition price of fuel rises before reaching Rp. 7.193, - / kg and higher after rising fuel reaching Rp. 8.000, - / Kg. While the total cost of fuel rises higher after than before rising fuel reaching Rp. 9.984.350 million, - / ha, and before rising fuel which only reached Rp. 8.668.000 million, - / ha, and income before rising fuel reaches Rp. 8.173.740 million, - / ha, while revenue rose higher fuel after the peak at USD. 8.185.420 million, - / Ha.